Whey Protein Isolate-Supplemented Beverage, Fermented by Lactobacillus casei BL23 and Propionibacterium freudenreichii 138, in the Prevention of Mucositis in Mice - Cordeiro, Bárbara F.; Oliveira, Emiliano R.; da Silva, Sara H.; Savassi, Bruna M.; Acurcio, Leonardo B.; Lemos, Luisa; Alves, Juliana de L.; Carvalho Assis, Helder; Vieira, Angélica T.; Faria, Ana M. C.; Ferreira, Enio; Le Loir, Yves; et al. (Frontiers in Microbiology, 2018)
Mucositis is a clinically important gastrointestinal inflammatory infirmity, generated by antineoplastic drugs cytotoxic effects. The inflammatory process caused by this disease frequently leads to derangements in the alimentary tract and great malaise for the patient. Novel strategies are necessary for its prevention or treatment, as currently available treatments of mucositis have several limitations in relieving its symptoms. In this context, several research groups have investigated the use of probiotic bacteria, and in particular dairy bacterial strains. Compelling evidences reveal that milk fermented by certain probiotic bacteria has the capacity to ameliorate intestinal inflammatory disorders. In addition, innovative probiotic delivery strategies, based on probiotics incorporation into protective matrices, such as whey proteins, were able to increase the therapeutic effect of probiotic strains by providing extra protection for bacteria against environmental stresses. Therefore, in this study, we evaluated the role of the whey protein isolate (WPI), when added to skim milk fermented by Lactobacillus casei BL23 (L. casei BL23) or by Propionibacterium freudenreichii CIRM-BIA138 (P. freudenreichii 138), as a protective matrix against in vitro stress challenges. In addition, we investigated the therapeutic effect of these fermented beverages in a murine model of mucositis induced by 5-Fluorouracil (5-FU). Our results demonstrated that milk supplementation with 30% (w/v) of WPI increases the survival rate of both strains when challenged with acid, bile salts, high temperature and cold storage stresses, compared to fermented skim milk without the addition of WPI. Moreover, treatment with the probiotic beverages prevented weight loss and intestinal damages in mice receiving 5-FU. We conclude that the presence of WPI maximizes the anti-inflammatory effects of L. casei BL23, but not for P. freudenreichii 138, suggesting that whey protein enhancement of probiotic activity might be strain-dependent.